2011
DOI: 10.1109/tpwrs.2010.2046503
|View full text |Cite
|
Sign up to set email alerts
|

Robust Detection and Analysis of Power System Oscillations Using the Teager-Kaiser Energy Operator

Abstract: Critical to real-time oscillations monitoring is early detection when otherwise dormant natural modes become a serious threat to grid stability. The next urgent issue is to determine the frequency and damping of the problematic modes when the signal is embedded in noise and the system contains closely spaced natural modes. The present paper addresses the detection issue using the Teager-Kaiser energy operator (TKEO) which has shown to be a fast predictor of the instability onset time when applied to the output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 30 publications
(79 reference statements)
0
43
0
Order By: Relevance
“…Advanced signal processing techniques are therefore required to deal with the complexity and uncertainty associated with a smart grid. In [9][10][11][12][13], a Teager-Kaiser energy operator has been proposed for power system oscillations detection and analysis. However, this operator is highly affected by noises.…”
Section: Phasor Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced signal processing techniques are therefore required to deal with the complexity and uncertainty associated with a smart grid. In [9][10][11][12][13], a Teager-Kaiser energy operator has been proposed for power system oscillations detection and analysis. However, this operator is highly affected by noises.…”
Section: Phasor Estimationmentioning
confidence: 99%
“…These methods are based on electrical quantity signatures analysis (current, voltage, power, etc.) [9][10][11][12]; and usually involves the use of reference frame transformations such as Park's vector [13] or space vector [8][9][10][11][12][13][14]; other methods are based on advanced signal processing tools [15][16][17] where the EEMD is investigated; but the wellknown method is based on the symmetrical components transformation [18][19]. This work attempts to highlight the use of signal processing techniques for phasor estimation in the context of smart grids.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular include the Hilbert transform (HT) [16] and the Teager Energy Operator [17]. Furthermore for three-phase system, it has been recently shown that the Concordia transform can be used to perform demodulation [18].…”
Section: A Amplitude Demodulationmentioning
confidence: 99%
“…For modulated signals, the most popular techniques are TKEO [18], HT, and it has been recently shown that the CT can be used for demodulation [19][20]. Those techniques were investigated in many research works for failure detection tasks.…”
Section: Current Modulation Vs Failure Detection Techniquementioning
confidence: 99%